1972
DOI: 10.1007/bf00386501
|View full text |Cite
|
Sign up to set email alerts
|

Localization and uptake of 14C-IAA in relation to xylem regeneration in Coleus internodes

Abstract: 14C-IAA was applied to decapitated Coleus 5th internodes. Sections were radioautographed at various intervals after the application. The location of the label within cells and tissues is discussed. No accumulation of label occurred in the region where xylem cells regenerated. Label was particularly associated with xylem and phloem cytoplasm, but also occurred in other cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1974
1974
1998
1998

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Already differentiated tracheary cells (i.e., those radially farther from the cambium), as well as young tracheary cells longitudinally farther from the site of IAA application, are not labeled. Similar re-sults were later reported from other Coleus stocks (Wangermann, 1970;Gee, 1972).…”
Section: Hormone Movement and Action In Green Shootssupporting
confidence: 90%
“…Already differentiated tracheary cells (i.e., those radially farther from the cambium), as well as young tracheary cells longitudinally farther from the site of IAA application, are not labeled. Similar re-sults were later reported from other Coleus stocks (Wangermann, 1970;Gee, 1972).…”
Section: Hormone Movement and Action In Green Shootssupporting
confidence: 90%
“…The first label over the phloem was seen after 24 hours, and after 48 hours the cytoplasm and slime material were the predominantly labelled regions of the phloem. Further studies with Coleus using14 C-IAA showed heavy labelling in the phloem near the sieve plates and slime plugs, and the label could be removed by leaching(Wangermann, 1968(Wangermann, , 1970Gee, 1972). These re searches in Coleus indicate the possible involvement of phloem in the translocation of lAA.…”
mentioning
confidence: 98%